Bile ducts injury during laparoscopic cholecystectomy: current state of the problem - A. V. Vlasov; A. V. Panyushkin; I. M. Zhidkov; D. G. Baranova (Вестник хирургии имени И.И. Грекова)
Bile duct injuries occur in 0.4 % of elective and 0.8 % of emergency laparoscopic cholecystectomies. The risk factors for bile duct damage and the optimal timing of laparoscopic cholecystectomy were studied. The emphasis is on theoretical and practical training of the surgeon as the main component of the prevention of bile duct injuries. The variant anatomy of vessels, bile ducts and important anatomical landmarks during the operation are described. During «complex cholecystectomy», «rescue strategies» are proposed and modern imaging techniques are reviewed. The concept of safe cholecystectomy is evaluated. The issues of damage classification are touched upon. Analysis of the literature showed that debate continues in the global surgical community about the correct tactics for managing these patients. There is also a problem in assessing complications and there is a lack of standardization of outcomes after laparoscopic cholecystectomy.